1998
DOI: 10.1164/ajrccm.157.6.9711061
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Sustained-Release Morphine on Breathlessness and Quality of Life in Severe Chronic Obstructive Pulmonary Disease

Abstract: Morphine has been proposed as a treatment for breathlessness in patients with severe chronic obstructive pulmonary disease (COPD), but there is uncertainty as to whether or not it is effective. Orally administered sustained-release morphine was compared with placebo in a randomized, double-blind, crossover trial with two 6-wk treatment periods separated by a 2-wk washout period. The primary end point was quality of life measured using the Chronic Respiratory Disease Questionnaire (CRQ). Secondary end points in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
94
0
4

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(99 citation statements)
references
References 19 publications
1
94
0
4
Order By: Relevance
“…Short-term administration reduces breathlessness in patients with a variety of conditions, including advanced COPD (236,237), interstitial lung disease (238), cancer (239), and chronic heart failure (240). However, evidence of long-term efficacy is limited and conflicting (241,242). Opioids are associated with frequent side effects (241,243), particularly constipation, but clinically significant respiratory depression is uncommon with the doses used to treat dyspnea, even in elderly patients (244,245).…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Short-term administration reduces breathlessness in patients with a variety of conditions, including advanced COPD (236,237), interstitial lung disease (238), cancer (239), and chronic heart failure (240). However, evidence of long-term efficacy is limited and conflicting (241,242). Opioids are associated with frequent side effects (241,243), particularly constipation, but clinically significant respiratory depression is uncommon with the doses used to treat dyspnea, even in elderly patients (244,245).…”
Section: Treatmentmentioning
confidence: 99%
“…However, evidence of long-term efficacy is limited and conflicting (241,242). Opioids are associated with frequent side effects (241,243), particularly constipation, but clinically significant respiratory depression is uncommon with the doses used to treat dyspnea, even in elderly patients (244,245). Randomized controlled trials have not found nebulized opioids to be associated with fewer side effects than oral or parenteral opioids (246).…”
Section: Treatmentmentioning
confidence: 99%
“…Dose titration stopped at 30mg per 24 hours given the levels of toxicity reported in a earlier study that used higher doses of opioids in the chronic setting. [21] These results may under-represent the net clinical benefit. As with pain, people may increase activity as the symptom is better controlled but report only marginal improvement in the symptom itself.…”
Section: Limitations Of the Study -Designmentioning
confidence: 99%
“…Recent neuroimaging studies suggest that neural pathways involved in pain and dyspnea sensation may be shared and, therefore, similar neurophysiological and psychological approaches used to understand and manage pain can be applied to dyspnea (Nishino, 2011). Previous randomised controlled trials have reported the effectiveness of sustained-release morphine in patients with refractory dyspnea, including those with severe COPD (Abernethy et al, 2003;Poole et al, 1998) and chronic heart failure (Johnson et al, 2002). Currently there is no data on use of opioids to relieve dyspnea in patients with progressive advanced PAH and clinical trials are on-going.…”
Section: Palliative and Supportive Treatments For Residual Dyspnea Inmentioning
confidence: 99%